2007
DOI: 10.1172/jci31399
|View full text |Cite
|
Sign up to set email alerts
|

Improved prediction of prostate cancer recurrence through systems pathology

Abstract: We have developed an integrated, multidisciplinary methodology, termed systems pathology, to generate highly accurate predictive tools for complex diseases, using prostate cancer for the prototype. To predict the recurrence of prostate cancer following radical prostatectomy, defined by rising serum prostate-specific antigen (PSA), we used machine learning to develop a model based on clinicopathologic variables, histologic tumor characteristics, and cell type-specific quantification of biomarkers. The initial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 44 publications
0
86
2
Order By: Relevance
“…Therefore, it is essential new markers be developed, ideally based upon pathological analysis of the tissue and thus available immediately following surgery. To this end, recent studies have demonstrated this approach accurately predicts PSA recurrence, 20 but whether it accurately predicts more delayed end-points remains to be determined. However, given the limitations that not all men have PSADT data, it is clear that this approach is desperately needed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential new markers be developed, ideally based upon pathological analysis of the tissue and thus available immediately following surgery. To this end, recent studies have demonstrated this approach accurately predicts PSA recurrence, 20 but whether it accurately predicts more delayed end-points remains to be determined. However, given the limitations that not all men have PSADT data, it is clear that this approach is desperately needed.…”
Section: Discussionmentioning
confidence: 99%
“…They have also shown that this observation is similar to that of breast cancer, where the loss of ZAG production was associated with the lack of tumor differentiation. It is interesting to note that the expression of ZAG in prostate cancer is similar to that of other relevant prostatic proteins (57), such as prostate-specific antigen and prostatic acid phosphatase, which are significantly decreased in prostatic tumors (63)(64)(65). Moreover, immunohistochemical studies assured the partial loss of ZAG expression in prostatic tissue after malignant transformation (47).…”
Section: Zag and Cancermentioning
confidence: 99%
“…In principle, suitable combinations of markers may be successful in cumulatively predicting outcome, as enabled by new technologies such as molecular systems pathology (Cordon-Cardo et al 2007). Alternatively, system biology approaches that identify master regulatory genes of disease progression may enable the effective stratification of patients, as has been applied for other cancer types (Carro et al 2009).…”
Section: Biomarker Discoverymentioning
confidence: 99%